Penggunaan Aplikasi Zoom Cloud Meeting pada Proses Pembelajaran Online Sebagai Solusi di Masa Pandemi Covid 19 - Fitriyani Fitriyani; Marisa Deza Febriyeni; Nurlila Kamsi (STAI Bumi Silampari, 2020)
This article depicts a slightly different educational pattern due to the outbreak of the disease, which came into Indonesia since the beginning of last March. Impact on the whole order in Indonesia, such as economic, political, social, and even impact the education system. Since the circular letter issued by the government that all students/students to do distance learning and by using via online. So between teachers and students need a bridge to keep learning active even in the middle of pandemic. A cloud meeting's zoom application, as if to be a new class in the learning process and the application also becomes a solution for learning at school to run properly. Despite the many students who complained about this online learning. But this pattern of modern education should still be implemented until the return state is conducive.